Pengaruh Likuiditas, Leverage dan Profitabilitas terhadap Kualitas Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2016-2022 - Desi Qonita; Listiorini Listiorini; Liza Novietta (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of Liquidity, Leverage, Profitability on Quality Of Income with Company Size as a moderating variable. This type of research is a type of quantitative research. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used was purposive sampling with a sample of 59 companies with 5 years of observation so that the total sample was 295. The data analysis technique of this research used Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA) using residual test.The results of this study indicate that Liquidity and Profitability have a significant effect on Quality Of Income, while Leverage have no effect on Quality Of Income. Company Size is able to moderate the influence of Liquidity, Leverage and Profitability on Quality Of Income in Manufacturing Companies listed on the Stock Exchange. Indonesian Securities 2016-2020 Period.